2017
DOI: 10.1111/rda.12911
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Gonad histology and serum 11‐KT profile during the annual reproductive cycle in sterlet sturgeon adult males, Acipenser ruthenus

Abstract: The aim of this study was to assess monthly testicular development in the cultured breeding stock of sterlet, Acipenser ruthenus, using histological and serum sex steroid changes. Testicular development in the adult male was examined monthly and showed four distinct phases including resting, pre-spawning, spawning and post-spawning. Also, seasonal changes of the testes were described according to its variations in gonadosomatic index (GSI) during different phases of testicular development. Using histology, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…The latter compartment, or interlobular tissue, was composed of connective tissue containing Leydig cells, myoid cells, macrophages, fibroblasts, collagen fibers, blood vessels and nerve fibers. The developmental stage of the mature testes examined corresponded to the pre‐spawning phase of A. ruthenus (Golpour et al, ) and to the same phase, identified as the reproductive stage IV, in S. platorynchus (Wildhaber et al, ).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The latter compartment, or interlobular tissue, was composed of connective tissue containing Leydig cells, myoid cells, macrophages, fibroblasts, collagen fibers, blood vessels and nerve fibers. The developmental stage of the mature testes examined corresponded to the pre‐spawning phase of A. ruthenus (Golpour et al, ) and to the same phase, identified as the reproductive stage IV, in S. platorynchus (Wildhaber et al, ).…”
Section: Resultsmentioning
confidence: 93%
“…Species of Acipenseridae are considered differentiated gonochorists, but hermaphroditism has been reported in one wild individual of the white sturgeon, Acipenser transmontanus Richardson, 1836 (Acipenseriformes: Acipenseridae) (Chapman, Van Eenennaam, & Doroshov, ), in farmed and artificially reproduced sterlet sturgeon, A. ruthenus Linnaeus, 1758 (Acipenseriformes: Acipenseridae) (Williot et al, ) and in wild individuals of the shovelnose sturgeon, Scaphirhynchus platorynchus (Rafinesque, 1820) (Acipenseriformes: Acipenseridae) captured in polluted waters (Harshbarger, Coffey, & Young, ). Intersexuality, a condition in which the male gonad contains oogonia or oocytes and the female gonad contains spermatogonia and spermatocytes, has been reported in wild Atlantic sturgeon, A. oxyrhinchus Mitchill, 1815 (Acipenseriformes: Acipenseridae) (Van Eenennaam & Doroshov, ) and also in farmed Siberian sturgeon, A. baerii Brandt, 1869 (Acipenseriformes: Acipenseridae) (Rzepkowska, Ostaszewska, Gibala, & Roszko, ), Russian sturgeon, A. gueldenstaedtii Brandt & Ratzeburg, 1833 (Acipenseriformes: Acipenseridae) (Jackson et al, ; Rzepkowska et al, ) and A. ruthenus (Golpour et al, ). In sturgeons, gonad sex differentiation requires between 3 and 15 months from birth according to species, geography, and environmental conditions (Akhundov & Fedorov, ; Alavi, Rodina, Gela, & Lihart, ).…”
Section: Introductionmentioning
confidence: 98%
“…However, sturgeons have no reliable external sexual characteristics, as previously described (Chebanov & Galich, ; Fopp‐Bayat, ). Currently, to determine sex, hormonal (Du et al, ; Mosyagina & Zelennikov, ; Wheeler, Novak, Wippelhauser, & Sulikowski, ), biochemical (Barulin, ; Yarmohammadi et al, ), histological methods (Golpour et al, ) and biopsy, laparoscopy (Falahatkar & Poursaeid, ; Webb, Eenennaam, Crossman, & Chapman, ), endoscopy (Munhofen, Jiménez, Peterson, Camus, Jiménez, Peterson, Camus, & Divers, ) are used. Above methods have difficulties with mass application in aquaculture and can have a high error (the first two methods) or can traumatize fish (the last four methods).…”
Section: Introductionmentioning
confidence: 99%
“…It can be used only in warmwater fish species (such as tilapia), where the proliferation of spermatogonia is initiated by increasing the temperature. However, in sturgeons the spermatogonia proliferation begins when the temperature decreases (in autumn) [10], thus making busulfan unsuitable for use on sturgeons. Furthermore, busulfan treatment is known to cause side effects in fish, and the efficiency of GSCs removal is not always perfect [11–13].…”
Section: Introductionmentioning
confidence: 99%